European Capital Markets and a Single Market Union - Chindendere, Brian (Digital Repository of Theses, 2026)
This dissertation critically examines the European Union's (EU) Capital Markets Union (CMU) initiative, evaluating its progress in creating a unified, efficient capital market across member states. By analyzing key regulatory frameworks, such as MiFID II and the Prospectus Regulation, as well as the development of the European Single Access Point (ESAP), the study highlights both the achievements and challenges in harmonizing capital markets. While notable strides have been made in improving transparency, reducing transaction costs, and enhancing cross-border investment flows, significant barriers remain, including legal fragmentation, political resistance, and demographic disparities in market participation. The research underscores the importance of adapting EU policies to local contexts and advancing digital infrastructure to foster broader market integration. Ultimately, the dissertation advocates for a more inclusive and flexible regulatory approach, emphasizing the need for deeper legal harmonization and greater support for underrepresented market participants to fully realize the CMU's potential. The European Union (EU) has long pursued the integration of capital markets to enhance economic cohesion, financial and global competitiveness. At the core of this ambition is the capital markets union (CMU), a strategic indicative aimed at creating a single, deep, and integrated market for capital across all EU member states. The aim is to ease cross border investments, reduce the fragmentation of financial markets, and improve access to finance for business, particularly small and medium sized enterprises (SMESs). Despite the excellent progress made since the CMU’s launch in2015, achieving a truly unified capital market is still a complex challenge. Regulatory discrepancies, diverse national legal frameworks, and differing tax regimes continue to hinder full integration. Brexit further complicated the landscape, as London previously the EU’s financial hub exited the Union, prompting a rebalancing of capital market activity toward cities like Frankfurt, Paris, and Amsterdam. The European Commision’s CMU Action Plans (2015) and 2020) outline a series of legislative and non legislative measures to address structural barriers. These include improving financial literacy, harmonizing insolvency laws, fostering fintech innovation, and enhancing supervision through bodies like the European Securities and Markets Authority (ESMA). A fully realized CMU is expected to complement the EU’s Banking Union and support the European Green deal and digital transition by channeling investment toward sustainable and innovative sectors. Creating a single capital market is not merely an economic project but a political one, requiring strong coordination, trust, and willingness among member states to cede certain aspects of national control. A unified market would significantly increase the EU’s ability to absorb shocks, diversify sources of financing and reduce reliance on bank landing. In conclusion, while large strides have been made toward a Capital Marker Union, the path to a fully integrated single capital market in the EU is still ongoing. Success hinges on continued political commitment, institutional cooperation, and the ability to harmonize financial regulation while respecting national differences. A cohesive capital market is essential for the EU to finance future growth, enhance resilience, and assert its role as a global financial player.